2005
DOI: 10.1016/j.jacc.2004.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of high-density lipoprotein cholesterol-increasing compounds

Abstract: Fibrates reduce major coronary events and increase HDL-C levels without significant toxicity. Niacin has a more potent effect on HDL-C levels, whereas data on cardiovascular event rate reduction are limited. Future studies need to evaluate whether additional HDL increase by fibrates or particularly newer niacin formulations on top of statin therapy translates into further event reduction in high-risk subjects, without significant toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
252
1
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(271 citation statements)
references
References 106 publications
(113 reference statements)
6
252
1
12
Order By: Relevance
“…They have been shown to raise HDL-cholesterol, lower total cholesterol and triglyceride concentrations and decrease LDL concentrations [20]. Several large scale trials of fibrate therapy have been completed, results, however, have been conflicting about the presence and magnitude of any cardiovascular protective effects.…”
Section: Introductionmentioning
confidence: 99%
“…They have been shown to raise HDL-cholesterol, lower total cholesterol and triglyceride concentrations and decrease LDL concentrations [20]. Several large scale trials of fibrate therapy have been completed, results, however, have been conflicting about the presence and magnitude of any cardiovascular protective effects.…”
Section: Introductionmentioning
confidence: 99%
“…In adipose tissue niacin inhibits the lipolysis of triglycerides by hormone-sensitive lipase. In previous systematic reviews, it has been associated with increased serum HDL-C [163] and reduction of cardiovascular events and stroke [164] but its routine use in prevention is controversial [165]. Its deficiency causes pellagra and its side effects are mainly represented by cutaneous flushing, dry skin, pruritus, skin rashes and achanthosis nigricans, as well as gout exacerbation and serious hepatotoxicity (high serum transaminases and hyperglicaemia [162]).…”
Section: Discussionmentioning
confidence: 99%
“…Deterioration of glucose tolerance, elevation of FBG concentrations and development of NODM have been reported with niacin use [31][32][33]. Birjmohun et al found the incidence of niacin-induced hyperglycemia to be around 2.3% in a meta-analysis including 30 trials with 4749 participants randomized to niacin or placebo [32].…”
Section: Niacinmentioning
confidence: 99%